Subacute postoperative atrial fibrillation after heart surgery: Incidence and predictive factors in cardiac rehabilitation - Vincenzo Rizza; Francesco Maranta; Lorenzo Cianfanelli; Iside Cartella; Francesco Maisano; Ottavio Alfieri; Domenico Cianflone (Journal of Arrhythmia)
Abstract Background Postoperative atrial fibrillation (POAF) is the most common arrhythmia following cardiac surgery (CS). It may occur between the 1st and the 4th postoperative day as acute POAF or between the 5th and the 30th as subacute (sPOAF). sPOAF is associated with higher thromboembolic risk, which consistently increase patients' morbidity. Neutrophil‐to‐lymphocyte ratio (NLR) is a low‐cost inflammatory index proposed as possible POAF predictor. Identification of patients' risk categories might lead to improved postoperative outcomes. Methods The aim was to assess the incidence of sPOAF and to identify possible predictors in patients performing cardiovascular rehabilitation (CR) after CS. A single‐center cohort study was performed on 737 post‐surgical patients admitted to CR on sinus rhythm. Continuous monitoring with 12‐lead ECG telemetry was performed. We evaluated the predictive role of anamnestic, clinical, and laboratory data, including baseline NLR. Results Subacute POAF was documented in 170 cases (23.1%). At the multivariate analysis, age (OR 1.03; p = .001), mitral valve surgery (OR 1.77; p = .012), acute POAF (OR 2.97; p < .001), and NLR at baseline (OR 1.13; p = .042) were found to be independent predictive factors of sPOAF following heart surgery. Conclusions sPOAF is common after CS. Age, mitral valve procedures, acute POAF, and preoperative NLR were proved to increase sPOAF occurrence in CR. NLR is an affordable and reliable parameter which might be used to qualify the risk of arrhythmias at CR admission. Identification of new predictors of postoperative atrial fibrillation may allow to improve patients' prognosis.